Analisis investasi serta pengaruhnya terhadap kesempatan kerja dan pertumbuhan ekonomi di Indonesia - Rizki, Muhammad; Haryadi, Haryadi (e-Journal Perdagangan Industri dan Moneter, 2021)
This study aims to analyze the development of investment, labor, and economic growth in Indonesia during the years 2000-2015 and analyze the effect of investment on labor and economic growth in Indonesia during 2000-2015. This study uses descriptive and quantitative methods. The quantitative descriptive analysis method analyzes the development of investment, labor, and economic growth in Indonesia during 2000-2015 and the independent variable (buy) on the dependent variable (employment opportunities and economic growth). Also, employment opportunities in Indonesia while GDP and economic development in Indonesia continue to increase and partially or individually investment in Indonesia has a significant effect on Indonesia's employment opportunities and economic growth. Â Keywords: Investment, Employment opportunity, Economic growth